PENGARUH COGNITIVE DAN AFFECTIVE ONLINE SHOPPING EXPERIENCE TERHADAP E-LOYALTY PADA GENERASI MILLENIAL YANG BERBELANJA DI SITUS BELANJA ONLINE - Ida Farida; Renny Risqiani Roesman (Jurnal Manajemen dan Pemasaran Jasa, 2019)
The purpose of this study is to examine the effect of online customer shopping experience on electronic satisfaction, electronic trust and electronic loyalty. The online customer experience is divided into cognitive and affective online shopping experiences. Data was collected from 143 respondents. The Structural Equation Model method is used to analyze data using hypothesis testing.The results showed that the state of cognitive experience had a strong influence on e-satisfaction but the state of affective experience did not have a significant effect on e-satisfaction. E-satisfaction has a significant influence on electronic trust and loyalty.The managerial implications of this research is that e-satisfaction plays an important role in building consumer trust and loyalty. To build e-satisfaction, the perceived customer experience is necessary especially the experience that comes from experiential cognitive state obtained customer. The limitations of this study are in terms of numbers that are less representative so that further research is expected to expand the area used as the object of study and increase the number of respondents to the study so that the results obtained are expected to be better.